基于ANSYS的矿用减速器箱体的优化设计 - 赵丽娟; 刘宏梅 (Jixie chuandong)
As the object of 1000kW gear box in Zhang-Jia kou coal-mechanism limited company,three-dimensional parametric entity model was bullied and analyzed by ANSYS software.The reducter case was optimized by OPT and ANSYS Parametric Design Language APDL to make its mass minimal,and its mass was reduced by 13.32%（426.846kg）.